ANALYSIS OF THE EFFECT OF MAGNETIC LOCATION AND ADDITION OF BERRIER FLUX ON BACK EMF VALUE ON PMSG 12S8P USING FEM METHOD - Nur Cholis; Rizki Noor Prasetyono (Program Studi Teknik Elektro Universitas Peradaban, 2022)
The purpose of the study was to determine the effect of variations in the placement of magnets and flux barriers on the back emf value in the 12S8P permanent magnet synchronous generator (PMSG) modeling. Process the output voltage (back emf) by varying the geometry of the magnet's location and adding a carrier flux to each variation of the magnet's geometry because magnets are one of the most important parts of the Permanent Magnet Synchronous Generator (PMSG). Where in this study there are 2 independent variables, namely the location of the magnet and the addition of a carrier flux. Where variations in the location of the magnet there are three variations, namely on the surface of the rotor, 2 mm below the surface of the rotor, and 4 mm below the surface of the rotor and each variation will be added with a flux barrier. While the dependent variable in this study is the back emf value. The data analysis technique used is a simple linear regression method, where the simulation results are then entered into MS.Excel and then processed using SPSS software. From the results of the study, it was concluded that the location of the magnet and the addition of a carrier flux could affect the Back EMF value, as indicated by the significance of the regression analysis of the dependent and independent variables 0.001 <0.05. From the Back EMF value data, the closer the magnet is to the stator or rotor surface, the greater the back EMF value, on the contrary, the farther the magnet is from the stator or rotor surface, the smaller the back emf value.